Epidemiological, clinical and hematological aspects of bovine anaplasmosis: a retrospective hospital-based study (2012-2021) - Guedes, Amanda Reges; Souto, Rodolfo José Cavalcanti; Soares, Gliére Silmara Leite; Conceição, Ângela Imperiano da; Cajueiro, Jobson Filipe de Paula; Souza, Maria Isabel de; Afonso, José Augusto Bastos; Mendonça, Carla Lopes de (Medicina Veterinária, 2023)
The aim was to carry out a retrospective study of bovine anaplasmosis diagnosed at the Bovine Clinic of Garanhuns, Federal Rural University of Pernambuco (CBG/UFRPE) from 2012 to 2021. A descriptive analysis was performed of the epidemiological, clinical, and hematological data of 230 clinical records of cattle of different age groups. The disease represented 79.9% of the hemoparasites diagnosed at the Institution. Females aged ? 24 months of taurine lineage and their crosses, reared under intensive and semi-intensive systems, were the most affected. A higher occurrence of the disease was observed in the months of August to December. The most frequently observed clinical findings were apathy, decreased appetite, icteric mucous membranes, and tachycardia. Spontaneous abortion occurred in 12.8% of pregnant cows. Hematological findings revealed regenerative anemia, and the severity of the anemia was associated with a greater intensity of bone marrow response. Antimicrobials (oxytetracycline LA and enrofloxacin) were effective in reducing parasitemia, which, together with blood transfusion, were essential for the patient's clinical improvement. Clinical resolution with hospital discharge occurred in 82.6% of patients, with a mean hospital stay of eight days. Anaplasmosis was the most frequent hemoparasitosis in CBG/UFRPE. It is important to provide guidance measures for producers in the region, especially at the end of the rainy season before the dry season, so that the diagnosis and disease treatment are carried out as early as possible, allowing a faster recovery and return of the animals to production, and thus minimizing the economic impact to the dairy basin of the state of Pernambuco.